Spanish adaptation of the Passion Toward Work Scale (PTWS) - Serrano-Fernández, María José; Boada-Grau, Joan; Gil-Ripoll, Carme; Vigil-Colet, Andreu (Anales de Psicología / Annals of Psychology, 2017)
Passion at work has a great influence on the occupational health of workers. Vallerand and his collaborators have defined two types of passion, Harmonious and Obsessive. In the first type, people feel obliged to carry out an activity but freely decide to do it and do so in harmony with other aspects of their lives. And in the second, although the person likes the activity, they feel obliged to take part in it because of internal circumstances that exercise control over them. In this context, the objective was to adapt Vallerand and Houlfort’s Passion towards Work Scale (PTW) into Spanish. The participants were 513 workers, selected through non-probability sampling. We used the FACTOR program (version 7.2) and SPSS 20.0. The results of the CFA (ESEM) for the PTW scale supported the two-factor model (Harmonious Passion and Obsessive Passion), presented adequate reliability and evidence of validity with Burnout, Irritation, Engagement and Self-Efficacy. The PTW Scale and Questionnaire are reliable and valid instruments, suitable for being used in Spanish.